Sport officials' strategies for managing interactions with players: Face-work on the front-stage. (November 2018) - Cunningham, Ian; Simmons, Peter; Mascarenhas, Duncan
Abstract: Communication is central to managing perceptions of fairness and performance in sport officiating. Most of the few studies that focus on sport official communication have been limited to 'one-way' impressions and decision communication and tend to neglect more dynamic, dialogic interactions with players. This study explored sport officials' identity concerns and motivations and ways officials adapt and accommodate 'face' in interactions with players. Design: Qualitative methodology. Method: Video elicitation interviews using an allo-confrontation approach were conducted with 8 male and 6 female sport officials from 7 different team sports representing novice to professional levels. Goffman's (1959; 1967) dramaturgical sociology of interaction was used to frame identity projections and context in officials' communication management strategies. Findings: Analysis of interview transcripts revealed three distinct ways officials' face concerns emerge and are managed in interactions with players including (1) anticipating players' reactions and modifying presentation of self, (2) asserting and preserving the officials' own face, and (3) giving and restoring players' face. When incompatible interactional exchanges occur in sport matches, officials use different defensive and corrective face-work strategies to assert, re-establish, or appropriate face statuses for themselves and players. Conclusions: The findings highlight the importance of dynamics and context in sport official communication. They also emphasise the need to maintain relationships, preserve and protect identities, whilst being strategic in interactions with players. We conclude that new conceptualisations are needed in sport official communication to build on current 'one-way' concepts that dominate officiating research and training. Highlights: Official-player interactions are largely unspoken co-constructions. Officials adapt and modify self-presentation according to context. Officials assert and maintain face for themselves and players. Officials have enduring styles to manage face protection for self and players.